Studies of human Armet and of pea aphid transcripts of saliva proteins and the Unfolded Protein Response - Balthazor, James (Kansas State University, 2015)
Armet is a bifunctional protein that is apparently universally distributed among multicellular animal species, vertebrate and invertebrate alike. A member of the Unfolded Protein Response, (UPR) Armet promotes survival in cells that are under endoplasmic-reticulum (ER) stress. I have carried out biophysical studies on human Armet looking for compounds that bind to Armet and hence could reduce its anti-apoptotic function, thus potentially joining the growing class of pro-apoptotic drugs. Performed primarily with 1H-15N HSQC NMR, ligand studies showed that approximately 60 of the 158 residues are potentially involved with binding. The 60 residues are distributed throughout both domains and the linker suggesting multi-domain interaction with the ligand. Circular dichroism studies showed heat denaturation in a two-step unfolding process with independent unfolding of both domains of Armet with Tm values near 68°C and 83 C with the C-terminal domain unfolding first, as verified by 1H-15N HSQC NMR measurements. I also provide the first identification of UPR transcripts in pea aphids, Acyrthosiphon pisum, the genetic model among aphids. I measured transcript abundance with hope of finding future transcriptional targets for pest mitigation. I identified 74 putative pea aphid UPR components, and all but three of the components have higher transcript levels in aphids feeding on plants than those that fed on diets. This activated UPR state is attributed to the need for saliva proteins for plant feeding. Because aphids are agriculturally significant pests, and saliva is pivotal to their feeding on host plants, genes that encode saliva proteins may be targets for pest mitigation. Here I have sought the aphid’s saliva proteome by combining results obtained in several laboratories by proteomic and transcriptomic approaches on several aphid species. With these data I constructed a tentative saliva proteome for the pea aphid by compiling, collating, and annotating the data from several laboratories. I used RNA-seq to verify the transcripts in pea aphid salivary glands, thus expanding the proposed saliva proteome from approximately 50 components to around 130 components, I found that transcripts of saliva proteins are upregulated during plant feeding compared to diet feeding.
Keywords: UPR; RNA-seq; Pea aphid; Armet; Saliva